Introduction to statistics through resampling methods and R - Good, Phillip I. (John Wiley & Sons, Inc., 2013)
"Intended for class use or self-study, the second addition of this text aspires like the first to introduce statistical methodology to a wide audience, simply and intuitively, through resampling from the data at hand. The methodology proceeds from chapter to chapter from the simple to the complex"--
Includes indexes. - Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Resampling (Statistics); Statistics; Statistics as Topic; Rééchantillonnage (Statistique); Statistiques; Statistique; statistics; MATHEMATICS; Probability & Statistics; General; Statistik; Resampling; R; Programm